Sentinel Lymph Node Biopsy in Patients with Thick Primary Cutaneous Melanoma: Patterns of Use and Underuse Utilizing a Population-Based Model. (10th January 2013) - Martinez, Steve R.; Shah, Dhruvil R.; Yang, Anthony D.; Canter, Robert J.; Maverakis, Emanual
Abstract : Background . Sentinel lymph node biopsy (SLNB) for thick cutaneous melanoma is supported by national guidelines. We report on factors associated with the use and underuse of SLNB for thick primary cutaneous melanoma. Methods . The Surveillance, Epidemiology, and End Results database was queried for patients who underwent surgery for thick primary cutaneous melanoma from 2004 to 2008. We used multivariate logistic regression models to predict use of SLNB. Results . Among 1, 981 patients, 833 (41.8%) did not undergo SLNB. Patients with primary melanomas of the arm (OR 2.07, CI 1.56–2.75;P < 0.001 ), leg (OR 2.40, CI 1.70–3.40;P < 0.001 ), and trunk (OR 1.82, CI 1.38–2.40;P < 0.001 ) had an increased likelihood of receiving a SLNB, as did those with desmoplastic histology (OR 1.47, CI 1.11–1.96;P = 0.008 ). A decreased likelihood of receiving SLNB was noted for advancing age ≥ 60 years (age 60 to 69: OR 0.58, CI 0.33–0.99, P = 0.047 ; age 70 to 79: OR 0.32, CI 0.19–0.54, P < 0.001 ; age 80 or more: OR 0.10, CI 0.06–0.16, P < 0.001 ) and unknown race/ethnicity (OR 0.21, CI 0.07–0.62;P = 0.005 ). Conclusions . In particular, elderly patients are less likely to receive SLNB. Further research is needed to assess whether use of SLNB in this population is detrimental or beneficial.